Computational Methodologies for the in vitro and in situ Quantification of Neutrophil Extracellular Traps - van Breda, Shane V.; Vokalova, Lenka; Neugebauer, Claire; Rossi, Simona W.; Hahn, Sinuhe; Hasler, Paul (Frontiers in Immunology, 2019)
Neutrophil extracellular traps (NETs) are a neutrophil defensive mechanism where chromatin is expelled together with antimicrobial proteins in response to a number of stimuli. Even though beneficial in many cases, their dysfunction has been implicated in many diseases such as rheumatoid arthritis and cancer. Accurate quantification of NETs is of utmost importance for correctly studying their role in various diseases, especially when considering them as therapeutic targets. Unfortunately, NET quantification has a number of limitations. However, recent developments in computational methodologies for quantifying NETs have vastly improved the ability to study NETs. Methods range from using ImageJ to user friendly applications and to more sophisticated machine-learning approaches. These various methods are reviewed and discussed in this review.